2020
DOI: 10.1111/os.12603
|View full text |Cite
|
Sign up to set email alerts
|

Influence of MicroRNA‐141 on Inhibition of the Proliferation of Bone Marrow Mesenchymal Stem Cells in Steroid‐Induced Osteonecrosis via SOX11

Abstract: Objective To investigate whether miR‐141 and the sex determination region of Y chromosome box 11 (SOX11) play roles in steroid‐induced avascular necrosis of the femoral head (SANFH), and to explore whether miR‐141 could target SOX11 to influence the proliferation of bone marrow mesenchymal stem cells (BMSC). Methods Bone marrow mesenchymal stem cells (BMSC) were isolated and cultured from 4‐week‐old Sprague Dawley rats. A flow cytometry assay was performed to identify BMSC. BMSC were divided into two groups: a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…A previous study has indicated that miRNA plays an crucial role in the osteogenic differentiation of BMSCs, and abnormal expression of miRNA molecules may affect this process ( 46 ). Our previous study revealed that miR-141 can inhibit proliferation in BMSCs ( 24 ). Nevertheless, the role of this miRNA in osteogenic differentiation is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has indicated that miRNA plays an crucial role in the osteogenic differentiation of BMSCs, and abnormal expression of miRNA molecules may affect this process ( 46 ). Our previous study revealed that miR-141 can inhibit proliferation in BMSCs ( 24 ). Nevertheless, the role of this miRNA in osteogenic differentiation is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…miR-141 is also associated with tissue repair and osteogenic differentiation ( 23 ). Indeed, miR-141 inhibits the proliferation of BMSCs; inhibition of miR-141 can promote the proliferation of BMSCs ( 24 ) and their osteogenic differentiation ( 5 ), possibly by targeting vitamin C transporter 2 ( 25 ). Therefore, the inhibition of miR-141 could be harnessed for the prevention and treatment of osteonecrosis caused by glucocorticoids.…”
Section: Introductionmentioning
confidence: 99%
“…Derived from 3-week-old SD rats (male,70 g, purchased from the Model Animal Research Center of Kunming Medical University), the mandibles ( Figure 1(c) ) were removed and the medullary cavity was exposed [ 28 ]. The medullary cavity was rinsed out using a 1 ml syringe loaded with the SD rat BMSC culture medium (Cyagen Biosciences, USA), and the rinse solution was transferred to a culture flask [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…They are known to regulate many different biological processes and play an important roles in cell proliferation, migration, and differentiation [ 25 ]. For example, miR141 was shown to inhibit rat BMSC proliferation in vitro by direct targeting of SRY-Box Transcription factor 11 (SOX11) [ 26 ]. miR19b-3p overexpression induces human BMSC proliferation and expression of osteogenic differentiation related proteins: Runt-related transcription factor 2 (RUNX2), collagen type 1, alpha 1 (COL1), and alkaline phosphatase (ALP) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, miR141 was shown to inhibit rat BMSC proliferation in vitro by direct targeting of SRY-Box Transcription factor 11 (SOX11) [ 26 ]. miR19b-3p overexpression induces human BMSC proliferation and expression of osteogenic differentiation related proteins: Runt-related transcription factor 2 (RUNX2), collagen type 1, alpha 1 (COL1), and alkaline phosphatase (ALP) [ 26 ]. miR335-5p promotes osteogenic differentiation by regulating Dickkopf-related protein 1 (DKK1), a known inhibitor of WNT signaling and osteogenic differentiation [ 27 ].…”
Section: Introductionmentioning
confidence: 99%